Stitching: Pen Gestures that Span Multiple Displays - Hinckley, Ken; Ramos, Gonzalo; Guimbretiere, Francois; Baudisch, Patrick; Smith, Marc (AVI '04 Proceedings of the working conference on Advanced visual interfaces, 2004)
Stitching is a new interaction technique that allows users to combine pen-operated mobile devices with wireless networking by using pen gestures that span multiple displays. To stitch, a user starts moving the pen on one screen, crosses over the bezel, and finishes the stroke on the screen of a nearby device. Properties of each portion of the pen stroke are observed by the participating devices, synchronized via wireless network communication, and recognized as a unitary act performed by one user, thus binding together the devices. We identify the general requirements of stitching and describe a prototype photo sharing application that uses stitching to allow users to copy images from one tablet to another that is nearby, expand an image across multiple screens, establish a persistent shared workspace, or use one tablet to present images that a user selects from another tablet. We also discuss design issues that arise from proxemics, that is, the sociological implications of users collaborating in close quarters.